Differently substituted benzothiadiazoles as charge-transporting emitters for fluorescent organic light-emitting diodes. (July 2019) - Gudeika, Dalius; Miasojedovas, Arunas; Bezvikonnyi, Oleksandr; Volyniuk, Dmytro; Gruodis, Alytis; Jursenas, Saulius; Grazulevicius, Juozas V.
Abstract: Carbazolyl- and 1, 2, 3, 4-tetrahydrocarbazolyl-substituted benzothiadiazoles were prepared by Pd-catalyzed Buchwald- Hartwig and Heck reactions. Photophysical, electrochemical, thermal, charge-transporting properties, and performance in organic light emitting diodes (OLEDs) of the derivatives with donor-π-acceptor-π-donor and donor-acceptor-donor structures are discussed. Photo- and electroluminescent properties of the studied compounds of carbazole and benzothiadiazole are very sensitive to their molecular structures. Their glass transition temperatures range from 145 to 191 °C. Investigation of photophysical properties revealed importance of intramolecular twisting on excited state deactivation. Emission of dilute solutions of the compounds in nonpolar solvents appears in the orange region with fluorescence quantum yields up to 0.6.4, 7-(Di (1, 2, 3, 4-tetrahydro)carbazolyl)-[2, 1, 3]-benzothiadiazole demonstrates phosphorescence and delayed fluorescence at room temperature. Solid-state ionization potentials of the materials range from 5.64 to 5.82 eV. The layer of 4, 7-(di ( tert -butyl)carbazolyl)-[2, 1, 3]-benzothiadiazole shows high hole drift mobility of 1.7 × 10 −3  cm 2 /V·s at an electric field of 5.3 × 10 5  V/cm and relatively high electron drift mobility of 5.7 × 10 −5  cm 2 /V·s at an electric field of 5.8 × 10 5  V/cm. Red OLEDs based of singlet emission with maximum external quantum efficiency values of 1.3 and 0.13% were achieved using new emitters. Much better electroluminescent performance was observed for the compound having donor-acceptor-donor structure relative to the compound with donor-π-acceptor-π-donor structure. Graphical abstract: Image 1 Highlights: Compounds of carbazole and benzothiadiazole were synthesized. They formed glasses with glass transition temperatures ranging from 145 to 191 °C. Hole and electron mobilities reached 10 −3 and 10 −5  cm 2 /V·s, respectively at high electric fields. 4, 7-(Di(1, 2, 3, 4-tetrahydro)carbazolyl)-[2, 1, 3]-benzothiadiazole demonstrated phosphorescence and delayed fluorescence at room temperature. Red fluorescent organic light-emitting diode showed maximum external quantum efficiencies of 1.3%.